A Comparison of Pharmaceutical Product Performance of Albuterol Inhalers Available in the United States and Those Obtained in a Mexican Border Town. (December 2015) - Nocella, Meira; Kilber, Emily; Witmer, Brittney; Karlage, Kelly; Myrdal, Paul
Background: American residents travel to Mexico to purchase medications for a fraction of US cost and frequently without prescription requirements. A previous bioequivalence study found differences in lung function measures between 2 brands of Mexican-manufactured albuterol inhalers (both 100 µg/puff). An investigation of the pharmaceutical performance of different inhalers available may illuminate why different clinical results may be observed and offer insight to consumer and provider expectations of such products.Objective: The purpose of this study is to provide some reasonable expectations for a medical tourist who shops in Mexico for albuterol metered dose inhalers (MDIs) or for their health care providers by comparing pharmaceutical product performance of the consumer-available brands.Methods: Five different albuterol MDI products were purchased in Nogales, Mexico. The albuterol content was quantified through high-performance liquid chromatography. The inhalers were analyzed to determine the amount of the albuterol dose that can be considered respirable and compared with the findings from 2 US innovator products.Results: The mean respirable mass for each brand of albuterol MDI was compared with that of the other 4 brands and the 2 US innovator products using Student's t test. All evaluations showed significant differences ( P < .05) except for 3 comparisons (Sacrusyt vs Assal, P = .89; Xeneric-S vs non-US Ventolin, P = .98; Victory vs US Proventil HFA, P = .06).Conclusion: Since pharmaceutical variability was found among the albuterol MDIs evaluated in this study, consumers and clinicians should appreciate possible differences in product performance of albuterol MDIs obtained in Mexico.